Bureaucratic Reform Acceleration of The Ministry of Religious Affairs Through Organizational Cultural Development - Haji, Rusno; Purwanti, Rini (Balai Diklat Keagamaan Ambon, 2024)
The evaluation of bureaucratic reform in the Ministry of Religious Affairs shows that its implementation has not yet shown significant progress, its application has not been evenly distributed throughout all work units and still needs to be improved. One of the reasons for the slow pace of bureaucratic reform in the Ministry of Religious Affairs is a lack of supportive organizational culture. This study aims to measure the Ministry of Religious Affairs' organizational culture development using the mixed method with a sequential explanation. Quantitative data analysis uses descriptive statistics and multivariate Confirmatory Factor Analysis (CFA) statistics, while qualitative data analysis uses root cause analysis with the fishbone analysis method. The results showed that the level of internalization of organizational values and work culture in the Ministry of Religious Affairs has become espoused values and beliefs but has not yet become an underlying assumption. The implementation of bureaucratic reform in the Central is still not a massive and systemic movement. This is because the Basic Values of the Ministry of Religious Affairs as the basis for ASN behavior and code of ethics have not been well socialized. In addition, the formulation of Basic Values as a reference in bureaucratic reform is still overlapping and difficult to understand. Thus, a Grand Design of the cultural development program is needed to accelerate Bureaucratic Reform in the Ministry of Religious Affairs.